2012
DOI: 10.1159/000336095
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture and Moxibustion Decrease Renal Sympathetic Nerve Activity and Retard Progression of Renal Disease in Rats

Abstract: Background/Aim: Chronic kidney disease (CKD) is an increasing major public health problem worldwide. The sympathetic nervous system and nitric oxide play an important role in the pathogenesis of CKD. Traditional Chinese medicine has accumulated thousands of years of therapeutic experiences. Electroacupuncture (EA) and moxibustion (MO) are two such therapeutic strategies. The aim of this study was to investigate the renal and hemodynamic effects of EA-MO in an experimental model of a CKD. Methods: Male Wistar r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 105 publications
0
15
0
2
Order By: Relevance
“…The effect of GA on blood pressure may have resulted from enhanced absorption of Ca 2+ , which may lower blood pressure due to stimulation of the Ca 2+ -sensingreceptor with subsequent vasodilation [26] and natriuresis due to inhibition of Na + ,K + ,2Cl - cotransport in the thick ascending limb [27]. Whatever mechanism involved, the decrease of proteinuria may delay the progression of renal disease [28], as proteinuria is an important parameter for the progression of renal disease [28,29,30,31,32,33,34,35,36,37]. …”
Section: Renal Effects Of Gum Arabicmentioning
confidence: 99%
“…The effect of GA on blood pressure may have resulted from enhanced absorption of Ca 2+ , which may lower blood pressure due to stimulation of the Ca 2+ -sensingreceptor with subsequent vasodilation [26] and natriuresis due to inhibition of Na + ,K + ,2Cl - cotransport in the thick ascending limb [27]. Whatever mechanism involved, the decrease of proteinuria may delay the progression of renal disease [28], as proteinuria is an important parameter for the progression of renal disease [28,29,30,31,32,33,34,35,36,37]. …”
Section: Renal Effects Of Gum Arabicmentioning
confidence: 99%
“…β endorphin inhibits rVLM activity, resulting in the suppression of the sympathetic nervous system, which reduces blood pressure [25]. The study by Paterno et al showed that BL23 (shenshu) can increase the NO serum level and that NO acts as a vasodilator [26].…”
Section: Discussionmentioning
confidence: 99%
“…It can also help control renal failure by blocking sympathetic nerve action or controlling blood pressure (Paterno et al . ).…”
Section: Moxibustionmentioning
confidence: 97%
“…Recently some studies showed that analgesic effects of moxabustion could be explained by opioid release theory (Uryu et al 2007). It can also help control renal failure by blocking sympathetic nerve action or controlling blood pressure (Paterno et al 2012).…”
Section: Moxibustionmentioning
confidence: 99%